Project Planning and Implementation in Public TVET Institutions in Nairobi County, Kenya - Gatibiri, David Gatimu; Kamau, John; Kibos, Kiprop (European Scientific Journal, ESJ, 2024)
This study aimed to determine the influence project planning has on implementation of projects in public TVET institutions in Nairobi County, Kenya, due to limited empirical evidence on the phenomenon. Hoshin's model of strategic planning made up the study’s theoretical framework. The study adopted an explanatory research design and was conducted in public TVET institutions in Nairobi County. The target population of 132 respondents for the study constituted Ministry of Education officials and top management and staff members of public TVET institutions who were selected using a multistage sampling approach. The sample size was 79 respondents while 72 respondents returned questionnaires. Data was collected using semi-structured questionnaires and analyzed using descriptive (measures of central tendency, measures of frequency, and measures of dispersion) and inferential statistics (correlation analysis and regression analysis). The study found that project planning (p=.000) has significant positive effect on project implementation. Therefore, this research concluded that planning is a significant predictor of project implementation success in public TVET institutions in Nairobi County. The study urges future research to explore other types of project management practices and how they influence project implementation.